Bedside Tested Ocular Motor Disorders in Multiple Sclerosis Patients. (30th April 2014) - Servillo, G.; Renard, D.; Taieb, G.; Labauge, P.; Bastide, S.; Zorzon, M.; Castelnovo, G.
Abstract : Background/Aims . Ocular motor disorders (OMDs) are a common feature of multiple sclerosis (MS). In clinical practice, if not reported by patients, OMDs are often underdiagnosed and their prevalence is underestimated. Methods . We studied 163 patients (125 women, 76.7%, 38 men, 23.3%; median age 45.0 years; median disease duration 10 years; median EDSS 3.5) with definite MS (n = 150, 92%) or clinically isolated syndrome (n = 13, 8%) who underwent a thorough clinical examination of eye movements. Data on localization of previous relapses, MS subtype, and MRI findings were collected and analyzed. Results . Overall, 111/163 (68.1%) patients showed at least one abnormality of eye movement. Most frequent OMDs were impaired smooth pursuit (42.3%), saccadic dysmetria (41.7%), unilateral internuclear ophthalmoplegia (14.7%), slowing of saccades (14.7%), skew deviation (13.5%), and gaze evoked nystagmus (13.5%). Patients with OMDs had more severe disability ( P = 0.0005 ) and showed more frequently infratentorial MRI lesions ( P = 0.004 ) . Localization of previous relapses was not associated with presence of OMDs. Conclusion . OMDs are frequent in patients with stable (no relapses) MS. A precise bedside examination of eye motility can disclose abnormalities that imply the presence of subclinical MS lesions and may have a substantial impact on definition of the diagnosis and on management of MS patients.